PROFIL KEMAMPUAN MATEMATIKA PADA MATERI BANGUN DATAR UNTUK SISWA SEKOLAH DASAR DI ERA KURIKULUM MERDEKA - Lamin; Neni Mariana; Hendratno; Nurul Istiq’faroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to map the profile of elementary school students' mathematical abilities in the material of plane figures in the context of the Independent Curriculum. One area that requires a good understanding of mathematical concepts is solving problems involving plane figures. Understanding plane figures as part of basic geometry helps students to understand and interact with the space around them, both practically and theoretically. The Independent Curriculum emphasizes learning that is more flexible, independent, and in accordance with students' needs. In the material of plane figures, students' abilities in identifying shapes, understanding the properties of plane figures, and solving geometric problems are the main focus. This study uses a quantitative descriptive method to analyze the results of students' mathematical ability tests in several elementary schools. The results showed that most students had a basic understanding of plane figures, but had difficulty in more complex geometric reasoning. This study also compared the results with previous studies that showed changes in students' understanding patterns in the context of the Independent Curriculum. Effective teaching strategies, such as problem-based approaches, the use of manipulatives, visualization, and repeated practice, can help students strengthen their understanding of mathematical concepts in the context of plane figures. It is necessary to conduct student-centered learning that is able to develop high-level thinking skills so that students are able to understand the concepts and principles of the material being studied and are able to solve the mathematical problems faced, especially in the material on flat shapes.